Effect of emblicaofficinalisagainst so2 induced hepatotoxicity in Wistarrats - MADHURI YADAV,; ASHA AGARWAL, (International Journal of Pharma and Bio Sciences, 2016)
Air pollution is the most serious environmental issue and becoming a threat to all over the world. SO2 is considered as one of the most poisonous and irritant gas because it alters the physiology, biochemistry and behavior of the living individuals. The present study has been conducted to demonstrate the remedial effect of Emblica officinalis against SO2 induced hepatotoxicity in albino rats. The twenty albino rats were grouped in three sets- control set (1) were kept in control conditions, while, rats of experimental set (2) were exposed to 80ppm of SO2 gas 1h/d for 30 and 60 days and rats of experimental set (3) were exposed to 80ppm of SO2 gas 1h/d with oral administration of Emblica officinalis fruits extracts (200mg/kg b.wt.) for 30 and 60 days respectively. The results of the present findings indicate that SO2 causes significant increase in total bilirubin (p<0.05), conjugated bilirubin (p<0.05) while non-significant increase in unconjugated bilirubin level in liver besides, significant decrease in serum total protein (p<0.001), serum albumin (p<0.05), globulin (p<0.05) and significant increase in serum enzymes ALP (p<0.001), AST(p<0.01), ALT(p<0.001) and GGT(p<0.01) in liver of albino rats. Oral administration of Emblica officinalis recovers all these alterations at their standard physiological level which is an indication of remedial effect of E. officinalis on SO2 induced hepatotoxicity.